The relationship between innovation and information technology on organizational performance - Noor Azinuddin, Ahmad (2015)
Organizational performance is important to the organization. This is because it will be the benchmark to the organization whether the organization achieves their vision and mission or not. In order to ensure the company stay competitive, the organizational performance can be as a determined in order to ensure that the organization could be successful in the future. Hence, the purpose of this study is to know the relationship between innovation and information technology on the organizational performance in Malaysian Public Listed Companies. A cross-sectional study was chosen for this study. There are two objectives in this study, first is to evaluate the relationship between innovation with organizational performance in Malaysian Public Listed Companies. Second is to examine the relationship between information technology and organizational performance in Malaysian Public Listed Companies. Data were gathered through the online questionnaire survey of organizations (n=31). A total of 214 questionnaires were distributed to the Malaysian public listed companies by email and only 31 questionnaires were returned for analysis. The data has been analysed by using Statistic Package for Social Sciences (SPSS). Regression results have shown the innovation has no relationship with the organizational performance. Meanwhile, the results indicated that information technology has a significant and positive relationship with organizational performance. The implications of this study is the organization need to use information technology in order to enhance the organizational performance of the company. Besides that, information technology is the important tool to make the work become more effective and at the same time, the company can stay competitive in the market